2020
DOI: 10.1093/nsr/nwaa115
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution-precipitation growth of uniform and clean two dimensional transition metal dichalcogenides

Abstract: Two-dimensional (2D) transition metal dichalcogenides (TMDCs) have attracted much interest and shown promise in many applications. However, it is challenging to obtain uniform TMDCs with clean surfaces, because of the difficulties in controlling the way the reactants are supplied to the reaction in the current chemical vapor deposition (CVD) growth process. Here, we report a new growth approach called “dissolution-precipitation” (DP) growth, where the metal sources are sealed inside glass substrates to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 47 publications
1
50
0
Order By: Relevance
“…[ 10 ] Among all these methods, chemical vapor deposition (CVD) has been considered as a promising method as it provides a relatively scalable and controllable way for growing TMDCs. [ 11–21 ] Current CVD method usually uses solid (such as metal oxides and sulfur powder) as precursors for the growth of TMDCs. However, due to the significant differences of vapor pressure between sulfur and metal oxides, the reaction usually needs precise control of temperature and pressure in order to achieve stable supply of precursors, leading to poor controllability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 ] Among all these methods, chemical vapor deposition (CVD) has been considered as a promising method as it provides a relatively scalable and controllable way for growing TMDCs. [ 11–21 ] Current CVD method usually uses solid (such as metal oxides and sulfur powder) as precursors for the growth of TMDCs. However, due to the significant differences of vapor pressure between sulfur and metal oxides, the reaction usually needs precise control of temperature and pressure in order to achieve stable supply of precursors, leading to poor controllability and reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group reported a dissolution-precipitation (DP) growth method to control the metal precursor, and obtained uniform monolayer TMDCs over the whole centimeter-scale substrate (Figure 3a). 12 Different from the traditional CVD process (Figure 3c), in the DP growth method, the metal precursor was first buried in a confined space between a piece of top thin and another piece of bottom thick glass. The metal precursor then diffused to the surface of the upper glass where it served as a reactant to grow TMDCs at high temperature.…”
Section: Controlling the Metal Precursormentioning
confidence: 99%
“…In a typical CVD system, the metal oxide and sulfur precursor share the same diffusion path which leads to the reaction both in the transmitting process and on the substrate, causing pollution on surface of the as-grown products. Many efforts have been done to solve this problem [77,80]. Inspired by the graphene growth method [81,82], carbon source is dissolved in the bulk or sub-surface of substrates like Cu or Ni, carbon atoms are precipitated on substrate surface to generate largearea uniform graphene.…”
Section: Growth Substratementioning
confidence: 99%
“…Inspired by the graphene growth method [81,82], carbon source is dissolved in the bulk or sub-surface of substrates like Cu or Ni, carbon atoms are precipitated on substrate surface to generate largearea uniform graphene. Cai et al [77] reported a "dissolutionprecipitation" (DP) growth method that achieved the dissolution of the required metal source into the glass substrate and succeeded in growing uniform monolayer transition metal dichalcogenides (TMDs). As shown in Fig.…”
Section: Growth Substratementioning
confidence: 99%